Respuesta :

Answer:

x = 6

y = -7

Step-by-step explanation:

The two equations are:

[tex]$ 10x - 3y = 81 \hspace{20mm} \hdots (1) $[/tex]

[tex]$ -5x - 7y = 19 \hspace{20mm} \hdots (2) $[/tex]

Multiplying equation (2) by 2, we get:

[tex]$ -10x - 14y = 38 $[/tex]

Adding this equation and Equation (1), we get:

[tex]$ - 17 y = 119 $[/tex]

y = - 7

Substituting the value of y = -7 in Equation (1), we get:

10x = 81 + 3(-7)

⇒ 10x = 81 - 21 = 60

x = 6

Therefore, the solution to the equations is: (x, y) = (6, -7).

ACCESS MORE